Influence of hemoglobinopathies and glucose-6-phosphate dehydrogenase deficiency on diagnosis of diabetes by HbA1c among Tanzanian adults with and without HIV: A cross-sectional study. - Belinda Kweka; Eric Lyimo; Kidola Jeremiah; Suzanne Filteau; Andrea M Rehman; Henrik Friis; Alphaxard Manjurano; Daniel Faurholt-Jepsen; Rikke Krogh-Madsen; George PrayGod; Douglas C Heimburger (PLoS ONE)
Introduction Hemoglobin A1c (HbA1c) is recommended for diagnosing and monitoring diabetes. However, in people with sickle cell disease (SCD), sickle cell trait (SCT), α-thalassemia or glucose-6-phosphate dehydrogenase (G6PD) deficiency, HbA1c may underestimate the prevalence of diabetes. There are no data on the extent of this problem in sub-Saharan Africa despite having high prevalence of these red blood cell disorders. Methods Blood samples from 431 adults in northwestern Tanzania, randomly selected from the prospective cohort study, Chronic Infections, Comorbidities and Diabetes in Africa (CICADA), were analysed for SCT/SCD, α-thalassemia and G6PD deficiency and tested for associations with the combined prevalence of prediabetes and diabetes (PD/DM) by HbA1c, using the HemoCue 501 HbA1c instrument, and by 2-hour oral glucose tolerance test (OGTT). Results The mean age of the participants was 40.5 (SD11.6) years; 61% were females and 71% were HIV-infected. Among 431 participants, 110 (25.5%) had SCT and none had SCD. Heterozygous α-thalassemia (heterozygous α+ AT) was present in 186 (43%) of the participants, while 52 participants (12%) had homozygous α-thalassemia (homozygous α+ AT). Furthermore, 40 (9.3%) participants, all females, had heterozygous G6PD deficiency while 24 (5.6%) males and 4 (0.9%) females had hemizygous and homozygous G6PD deficiency, respectively. In adjusted analysis, participants with SCT were 85% less likely to be diagnosed with PD/DM by HbA1c compared to those without SCT (OR = 0.15, 95% CI: 0.08, 0.26, P < 0.001). When using OGTT, in adjusted analysis, SCT was not associated with diagnosis of PD/DM while participants with homozygous α+ AT and hemizygous G6PD deficiency were more likely to be diagnosed with PD/DM. Conclusions HbA1c underestimates the prevalence of PD/DM among Tanzanian adults with SCT. Further research using other HbA1c instruments is needed to optimize HbA1c use among populations with high prevalence of hemoglobinopathies or G6PD deficiency.